Data reporting standards: making the things we use better - Quackenbush, John (BioMed Central, 2009)
Genomic data often persist far beyond the initial study in which they were generated. But the true value of the data is tied to their being both used and useful, and the usefulness of the data relies intimately on how well annotated they are. While standards such as MIAME have been in existence for nearly a decade, we cannot think that the problem is solved or that we can ignore the need to develop better, more effective methods for capturing the essence of the meta-data that is ultimately required to guarantee utility of the data.